Construction and validation of prognostic nomograms for elderly patients with metastatic non‐small cell lung cancer. (5th May 2022) - Sun, Haishuang; Liu, Min; Yang, Xiaoyan; Ren, Yanhong; Dai, Huaping; Wang, Chen
Abstract: Background: Metastatic non‐small cell lung cancer (NSCLC) is mostly seen in older patients and is associated with poor prognosis. There is no reliable method to predict the prognosis of elderly patients (≥60 years old) with metastatic NSCLC. The aim of our study was to develop and validate nomograms which accurately predict survival in this group of patients. Methods: NSCLC patients diagnosed between 2010 and 2015 were all identified from the Surveillance, Epidemiology, and End Results (SEER) database. Nomograms were constructed by significant clinicopathological variables ( p  < 0.05) selected in multivariate Cox analysis regression. Results: A total of 9584 patients met the inclusion criteria and were randomly allocated in the training ( n  = 6712) and validation ( n  = 2872) cohorts. In training cohort, independent prognostic factors included age, gender, race, grade, tumor site, pathology, T stage, N stage, radiotherapy, surgery, chemotherapy, and metastatic site ( p  < 0.05) for lung cancer‐specific survival (LCSS) and overall survival (OS) were identified by the Cox regression. Nomograms for predicting 1‐, 2‐, and 3‐years LCSS and OS were established and showed excellent predictive performance with a higher C‐index than that of the 7th TNM staging system (LCSS: training cohort: 0.712 vs. 0.534; p  < 0.001; validation cohort: 0.707 vs. 0.528; p  < 0.001; OS: training cohort: 0.713 vs. 0.531; p  < 0.001; validation cohort: 0.710 vs. 0.528; p  < 0.001). The calibration plots showed good consistency from the predicted to actual survival probabilities both in training cohort and validation cohort. Moreover, the decision curve analysis (DCA) achieved better net clinical benefit compared with TNM staging models. Conclusions: We established and validated novel nomograms for predicting LCSS and OS in elderly patients with metastatic NSCLC with desirable discrimination and calibration ability. These nomograms could provide personalized risk assessment for these patients and assist in clinical decision. Abstract : A total of 9, 584 patients were used for the construction of the nomograms according to the inclusion criteria and the model demonstrated excellent predictive performance.